Método de agrupamento hierárquico a partir de currículos acadêmicos - Santos, Saulo Daniel dos (2017)
The Lattes platform has been used by universities, development agencies and research groups as the main source of information on researchers’ academic history, influencing curriculum analysis. Due to this fact, it is practically obligatory in Brazil that all researchers keep their curricula duly updated in this platform. Faced with this, many researchers explore this basis of curricula to discover new knowledge about the construction of science in Brazil.In this sense, the ScriptLattes tool has been widely used throughout the national territory by a range of researchers, to extract information from the curricula registered on the Lattes platform. The results obtained so far have been of great value for the extraction of knowledge from this basis of curricula. Based on the above, this work makes use of ScriptLattes to extract curriculum information from the Lattes platform. Thus, hierarchical clustering concepts are applied to construct a method for constructing group hierarchies. Based on this method, applications were built to:(i) produce reports that help fill the Sucupira and e-Mec platforms; (ii) to visualize similarities among postgraduate programs through area indicators.